Resource Use Efficiency of Irrigated Farms in Borunda Tube-Well Command Area, Rajasthan - Vyas, D L (Annals of Arid Zone, 2016)
This study was initiated to document the comparative use-pattern of resources in arid areas where water has recently been made available. The results revealed that whereas, water and tractor use could be profitably used, labour, land and nitrogenous fertilizers could generate profitable use only if the intensity of cropping is increased.